2011
DOI: 10.1371/journal.pntd.0000986
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Trachoma and Infection in Aboriginal Communities

Abstract: BackgroundTrachoma is the leading infectious cause of blindness due to conjunctival infection with Chlamydia trachomatis. The presence of active trachoma and evidence of infection are poorly correlated and a strong immunologically-mediated inflammatory response means that clinical signs last much longer than infection. This population-based study in five Aboriginal communities endemic for trachoma in northern Australia compared a fine grading of clinical trachoma with diagnostic positivity and organism load.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Furthermore, Michel et al found in 201126 that the sensitivity of a similar DRW-manufactured chlamydia lipopolysaccharide POC test for ocular trachoma was 30.4%, substantially less than the 83.6% published earlier by Michel et al 27; the difference was explained by a lower organism load. In an independent study, also published in 2011, Harding-Esch et al 28 found that the sensitivities of this test ranged between 33.3% and 67.9%.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, Michel et al found in 201126 that the sensitivity of a similar DRW-manufactured chlamydia lipopolysaccharide POC test for ocular trachoma was 30.4%, substantially less than the 83.6% published earlier by Michel et al 27; the difference was explained by a lower organism load. In an independent study, also published in 2011, Harding-Esch et al 28 found that the sensitivities of this test ranged between 33.3% and 67.9%.…”
Section: Discussionmentioning
confidence: 87%
“…4,6,13,[20][21][22] Photo grading has advantages over field grading. (1) Exam conditions can be standardized.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Individual-and community-randomized clinical trials have typically had clinical exam as primary or secondary outcomes. [4][5][6][7][8][9] Unfortunately, grading of clinical trachoma can have considerable variability. Even with rigorous training, different examiners grade cases differently.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies continue to find that actual rates of clinical signs in children are higher than actual infection rates. [30, 31]. …”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Latent class analysis suggests that clinical signs may be relatively sensitive, but that NAATs are far more specific. [33] Point-of-care (POC) assays of chlamydial lipopolysacchrides have yet to be found reliable in hot, humid environments [30,35]. …”
Section: Diagnosis and Treatmentmentioning
confidence: 99%